The transcription factor SOX18 regulates the expression of matrix metalloproteinase 7 and guidance molecules in human endothelial cells. - Martina Hoeth; Heide Niederleithner; Renate Hofer-Warbinek; Martin Bilban; Herbert Mayer; Ulrike Resch; Christof Lemberger; Oswald Wagner; Erhard Hofer; Peter Petzelbauer; Rainer de Martin (PLoS ONE)
Background Mutations in the transcription factor SOX18 are responsible for specific cardiovascular defects in humans and mice. In order to gain insight into the molecular basis of its action, we identified target genes of SOX18 and analyzed one, MMP7, in detail. Methodology/principal findings SOX18 was expressed in HUVEC using a recombinant adenoviral vector and the altered gene expression profile was analyzed using microarrays. Expression of several regulated candidate SOX18 target genes was verified by real-time PCR. Knock-down of SOX18 using RNA interference was then used to confirm the effect of the transcription factor on selected genes that included the guidance molecules ephrin B2 and semaphorin 3G. One gene, MMP7, was chosen for further analysis, including detailed promoter studies using reporter gene assays, electrophoretic mobility shift analysis and chromatin-immunoprecipitation, revealing that it responds directly to SOX18. Immunohistochemical analysis demonstrated the co-expression of SOX18 and MMP7 in blood vessels of human skin. Conclusions/significance The identification of MMP7 as a direct SOX18 target gene as well as other potential candidates including guidance molecules provides a molecular basis for the proposed function of this transcription factor in the regulation of vessel formation.